Conduction system pacing, a European survey: insights from clinical practice - Keene, Daniel; Anselme, Frédéric; Burri, Haran; Pérez, Óscar Cano; Čurila, Karol; Derndorfer, Michael; Foley, Paul; Gellér, László; Glikson, Michael; Huybrechts, Wim; Jastrzebski, Marek; Kaczmarek, Krzysztof; et al. (Europace, 2023)
AIMS: The field of conduction system pacing (CSP) is evolving, and our aim was to obtain a contemporary picture of European CSP practice. METHODS AND RESULTS: A survey was devised by a European CSP Expert Group and sent electronically to cardiologists utilizing CSP. A total of 284 physicians were invited to contribute of which 171 physicians (60.2%; 85% electrophysiologists) responded. Most (77%) had experience with both His-bundle pacing (HBP) and left bundle branch area pacing (LBBAP). Pacing indications ranked highest for CSP were atrioventricular block (irrespective of left ventricular ejection fraction) and when coronary sinus lead implantation failed. For patients with left bundle branch block (LBBB) and heart failure (HF), conventional biventricular pacing remained first-line treatment. For most indications, operators preferred LBBAP over HBP as a first-line approach. When HBP was attempted as an initial approach, reasons reported for transitioning to utilizing LBBAP were: (i) high threshold (reported as >2 V at 1 ms), (ii) failure to reverse bundle branch block, or (iii) > 30 min attempting to implant at His-bundle sites. Backup right ventricular lead use for HBP was low (median 20%) and predominated in pace-and-ablate scenarios. Twelve-lead electrocardiogram assessment was deemed highly important during follow-up. This, coupled with limitations from current capture management algorithms, limits remote monitoring for CSP patients. CONCLUSIONS: This survey provides a snapshot of CSP implementation in Europe. Currently, CSP is predominantly used for bradycardia indications. For HF patients with LBBB, most operators reserve CSP for biventricular implant failures. Left bundle branch area pacing ostensibly has practical advantages over HBP and is therefore preferred by many operators. Practical limitations remain, and large randomized clinical trial data are currently lacking.
Keywords: Heart Failure; srdeční resynchronizační terapie; Stroke Volume; Bundle-Branch Block; blokáda Tawarova raménka; funkce levé komory srdeční; převodní systém srdeční; Heart Conduction System; Cardiac Resynchronization Therapy; lidé; srdeční selhání; Treatment Outcome; tepový objem; výsledek terapie; srdeční arytmie; Ventricular Function, Left; Arrhythmias, Cardiac; Humans